2021
DOI: 10.1002/jum.15860
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Algorithms for Classification of First‐Trimester Fetal Brain Ultrasound Images

Abstract: Objective-To evaluate the feasibility of machine learning (ML) tools for segmenting and classifying first-trimester fetal brain ultrasound images.Methods-Two image segmentation methods processed high-resolution fetal brain images obtained during the nuchal translucency scan: "Statistical Region Merging" (SRM) and "Trainable Weka Segmentation" (TWS), with training and testing sets in the latter. Measurement of the fetal cerebral cortex in original and processed images served to evaluate the performance of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…16 (29%) studies reported the computational time, and 7 (13%) studies reported what kind of computational hardware was used. 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 Computation time ranged from 70 micro seconds to 25 min. 32 , 35 Next, we discuss the studies per topic in the following order: biometry, standard plane detection, segmentation, and together: growth models, abnormality detection, quality enhancement and visualization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…16 (29%) studies reported the computational time, and 7 (13%) studies reported what kind of computational hardware was used. 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 Computation time ranged from 70 micro seconds to 25 min. 32 , 35 Next, we discuss the studies per topic in the following order: biometry, standard plane detection, segmentation, and together: growth models, abnormality detection, quality enhancement and visualization.…”
Section: Resultsmentioning
confidence: 99%
“…The fetal head in the TV plane was segmented by five studies. 38 , 40 , 68 , 69 , 70 Three of those used the aforementioned HC18 challenge dataset. 40 , 44 , 68 , 69 Furthermore, four studies segmented the cerebellum, 39 , 41 , 71 , 72 and three studies segmented the choroid plexus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In medical image analysis, a number of studies have explored video classification and analysis methods for secondtrimester fetal ultrasound anomaly scan [10]. These include image-based segmentation [11]- [14], frame classification [15], [16], fetal biometry [17], [18] and tracking [19]. Several recent studies have explored obstetric ultrasound standard plane detection [20]- [23], automated biometry [13], [18], [24], [25], activity captioning [26]- [28] and visual attention modelling [20].…”
Section: Related Workmentioning
confidence: 99%
“…In contrast, only a few first trimester US image analysis studies have been undertaken with a different focus: automated CRL and NT measurements [38], assessment of the maternal placenta [39], classification of fetal brain images [40] and fetal echocardiography [41]. As exemplars of the state of art, Mathewlynn et al [42] proposed a fully automated placental volume and vascularity measurements method.…”
Section: Related Workmentioning
confidence: 99%